Shades of trade: Dark trading and price efficiency - Egginton, Jared F.; McBrayer, Garrett A.; Watson, Ethan D. (Journal of Banking & Finance, 2023)
Using a comprehensive approach, we investigate how various forms of non-displayed order flow such as hidden orders on exchanges, brokerage internalizations, and orders submitted to off-exchange venues affects price efficiency. By considering the multiple forms of dark trading available to traders, we are able to better understand the nuances of dark trading, its impacts on price efficiency, and mitigate the unobserved variable problems present in studies that examine only one aspect of dark trading. We find that hidden orders on exchange have a deleterious impact on price efficiency. The impacts of other types of pre-trade, non-displayed orders on price efficiency is more nuanced.